PENGARUH PENGUNGKAPAN ESG, RISIKO HUTANG, DAN INTENSITAS MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Kasus pada Perusahaan BUMN Tahun 2021-2023) - Razaysa Alika Khansa; Endang Kiswara (Diponegoro Journal of Accounting, 2026)
This study aims to examine and analyze the effect of ESG disclosure on the financial performance of state-owned enterprises (SOEs) in 2021–2023, the effect of leverage on the financial performance of state-owned enterprises (SOEs) in 2021–2023, and the effect of capital intensity on the financial performance of state-owned enterprises (SOEs) in 2021–2023. The population of this study was state-owned enterprises (SOEs) in 2021–2023. The sample was selected using a simple random sampling method that met the following criteria: The research subjects were state-owned enterprises (SOEs) in 2021–2023, SOEs that published annual reports and sustainability reports consecutively for the 2021–2023 period, and SOEs that used the Global Reporting Index (GRI) to prepare their sustainability reports for 2021–2023. The data used in this study were secondary data, with Eviews data analysis techniques. Based on the analysis of State-Owned Enterprises (SOEs) consistently from 2021 to 2023, several conclusions can be drawn: (1) The study shows that ESG disclosure does not have a significant impact on financial performance, therefore, hypothesis H1 is rejected. (2) The study shows that leverage has a negative and significant impact, therefore, hypothesis H2 is accepted. (3) The study shows that capital intensity has a positive and significant impact on financial performance, therefore, hypothesis H3 is accepted.